Role of microplastics in the survival and antimicrobial susceptibility of Campylobacter jejuni - Ortega-Sanz, Irene; Rajkovic, Andreja (Frontiers in Microbiology, 2026)
Microplastics (MPs) are a global concern due to their persistence in the environment and capacity to carry pollutants and pathogenic microorganisms. Given recent evidence on the co-occurrence of MPs and Campylobacter spp., the leading cause of foodborne gastrointestinal infections worldwide, this study investigates the role of MPs in Campylobacter jejuni contamination and their impact on antimicrobial susceptibility. The potential of five C. jejuni isolates from different origin (poultry, water, and human) to form biofilms on MPs over time (24 h, 48 h, and 72 h) was evaluated using traditional culture-dependent methods, including the reference strain C. jejuni subsp. jejuni strain NCTC 11168. The effect of MPs on the antimicrobial susceptibility of C. jejuni cells detached from MP-associated biofilms was also assessed using Etest strips. To comprehensively understand the interactions between the MPs and the bacteria, whole-genome sequencing was performed to explore the presence of adherence and biofilm-associated genes, as well as antibiotic resistance genes. The strains rapidly colonized the MPs within 24 h, exhibiting varying attachment densities over time ranging from 1.09 to 5.78 log CFU/MP, with strain NCTC 11168 identified as the strongest biofilm former overall. Furthermore, the abundance of adherence and biofilm formation genes was consistent with their abilities to form biofilm on MPs. The gene peb3 played a critical role in determining biofilm formation levels on MPs, while specific combinations of capA, capB, cj1725, and porA were linked to enhanced biofilm development. Similarly, the presence of antibiotic resistance determinants aligned with the phenotypic resistance, and only one strain (ST-6209/CC464) exhibited resistance to ciprofloxacin, nalidixic acid, and tetracycline. Notably, antimicrobial susceptibility of cells detached from MP-biofilms was increased by up to 4.6 log2-fold compared to planktonic counterparts. The findings indicate that MPs can facilitate the persistence of C. jejuni in the environment while simultaneously increasing their susceptibility to antibiotics. Further research with larger cohorts is needed to validate these preliminary observations in order to support the development of effective policies addressing MP pollution and food safety.